The Development and Application of Computers and Information Technology in the Military - Zhang Yinxiong (ITM Web of Conferences)
In the context of the new era of information technology, military operations and research have become increasingly reliant on computers and informatization. Military organizations are adopting cutting-edge technologies such as artificial intelligence, big data analytics, and cyber warfare strategies. This paper aims to explore the development and application of computers and information technology in the military field. Firstly, the paper introduces the evolution and innovations of computer and information technology over the past half-century. It then discusses related disciplines, including big data, the Internet of Things (IoT), cloud computing, and sensor technologies, along with relevant concepts and practical applications, providing theoretical support for the research. The paper also presents the current state of military informatization among major countries and regions worldwide. Furthermore, it elaborates on the future trends and directions of computer and information technology in the military. Finally, the paper highlights the importance of military informatization for national defense security and territorial sovereignty and outlines future developmental directions.